The book of Eli - Washington, Denzel, 1954-; Oldman, Gary; Kunis, Mila, 1983-; Hughes Brothers (Burbank, CA : Warner Home Video, 2010)
A man travels across a post-apocalyptic American protecting a sacred book that holds secrets to the survival of humans.
Originally released as a motion picture in 2010.
Features: additional scenes, A lost tale : Billy.
Denzel Washington, Gary Oldman, Mila Kunis, Jennifer Beals, Ray Stevenson.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Sacred books -- Drama; Video recordings for the hearing impaired; Fiction films; Dystopian fiction; Feature films; Action and adventure films; Dystopian films